A response surface analysis investigation of the effects of (mis)alignment between interpersonal values and efficacies on interpersonal problems. Issue 6 (3rd May 2021) - Kehl, Madeline; Edershile, Elizabeth A.; Hopwood, Christopher J.; Wright, Aidan G. C.
Abstract: Objective: In this study we examined whether discrepancies between interpersonal values and interpersonal efficacies are associated with distress, and provide a framework through which similar questions regarding intrapersonal alignment may be investigated. Method: Using interpersonal circumplex scales, we assessed interpersonal values and efficacies in two large samples (undergraduate N = 1, 453, community N = 1, 099) and used response surface analysis to model the alignment of these variables and their association with interpersonal distress. Results: We found that there were significant positive relationships between larger mismatches and greater distress. We also found that extremity in both matches and mismatches predicted more distress. At a more specific level, people who valued warmth but reported low efficacy for warm behavior reported problems related to being too cold to others. Conclusion: This study highlights the value of elaborating within‐person discrepancies across personality levels, provides a model for doing so organized around the interpersonal circumplex, and specifies connections between value‐efficacy discrepancies and interpersonal distress.